High performance options trading : - Yates, Leonard (John Wiley & Sons, 2003)
Experts are praising High Performance Options Trading From OptionVue™ Systems' Len Yates "Finally! A book by fellow Boilermaker and option software guru Len Yates! This book is a must-read for anyone interested in a sensibly based, analytical approach to options trading-whether you're a stock or a future options trader. And the story behind the creation of OptionVue™ is a fascinating bonus." -Larry McMillan, McMillan Analysis Corp. author of Profit with Options and McMillan on Options "An expert on volatility-based trading, Len Yates applies the same practical approach to this book as he has to his highly regarded software. This is not a technician's white paper, but a thorough, accessible guide that uses his real-life trading history to fully illustrate how you can succeed in the options markets." -Jim Bittman, Senior Instructor, CBOE's Options Institute author of Trading Index Options and Options for the Stock Investor "For over two decades Len Yates has helped bring options to the masses by way of his groundbreaking software, OptionVue™ 5. Now, his new book offers the same user-friendly style and insight to the world of options investing. I'm sure I speak for thousands of grateful investors when I say, ‘Well done, Len!'" -Jon "Doctor J" Najarian, PTISecurities.com author of How I Trade Options "Len leads the reader through the complex subject of options by recounting his triumphs and defeats and explaining in plain English the essence of each strategy." -David Krell, President and CEO, International Securities Exchange (ISE) "A must-read for all options traders." -Paul Forchione, Opportunities in Options, Inc. "From a master of options analytics comes this practical guide to options trading. Beginning and advanced traders alike will appreciate Len's thorough coverage of options strategies and his easy-to-read style." -Price Headley, President, BigTrends.com author of Big Trends in Trading